PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KETERAMPILAN KOLABORASI SISWA SMP - Nita Dwi Indahsari; Habiddin Habiddin; Nita Dwi Indahsari (Universitas Negeri Malang, 2024)
Abstract:21st century skills have become a hot topic in recent years. Indonesian graduates today need more skills to compete in this era. One of the skills in the 4Cs is collaboration, which is the process of group learning to discuss differences in views and knowledge through discussion, suggestions, and appreciation for differences of opinion (Greenstein, 2012). Collaborative skills, such as group work and discussion, are very important for students. It helps them channel their energy to achieve a shared vision for solving problems (Hidayati, 2019). Collaborative skills need to be applied so that students are accustomed to socializing and ready to work with anyone in their future lives. This study aims to observe the effect of applying the Problem Based Learning (PBL) learning model in science subjects to improve the collaborative skills of students in class IX C of SMPN 7 Malang. This study uses the Classroom Action Research (CAR) method, which is carried out in two cycles. The results of the study show that the application of the PBL learning model is proven to be effective in improving students' collaborative skills. This is evidenced by the increase in the percentage of the four indicators of collaborative skills assessment, namely working productively, respecting each other, compromising, and sharing responsibility